Junior high school mathematics teachers’ knowledge in calculators - Isaac Bengre Taley; Matilda Sarpong Adusei (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2020)
Helping junior high school students to use calculators and computers for problem solving and investigating real-life situations is an objective of the junior high school mathematics curriculum in Ghana. Ironically, there is a technological drought in junior high school mathematics instruction in Ghana, with a suspicion that mathematics teachers’ competency in the use of calculators for teaching may be the source of this lack of use. This study sought to establish a correlation between junior high school mathematics teachers’ competence and the motivation supporting the use of calculators in teaching.  A descriptive survey comprising of a test and questionnaire was used to collect data from junior high school mathematics teachers in an educational district in Ghana. Teacher characteristics such as educational attainment, age, and gender in relation to teachers’ competency in the use of calculators were discussed in the study. The results showed that about 70% of the teachers exhibited a low level of calculator competence. Besides, novice teachers outperformed expert teachers in the calculator competency-based test. Additionally, mathematics teachers’ enthusiasm for using calculators in teaching was directly associated with the teachers’ level of competency. The findings may send a signal to stakeholders in their efforts to revising the Ghana JHS curriculum in order to actualize the curriculum desire for the integration of technology in the teaching and learning of JHS mathematics.